Outcomes associated with SARS-CoV-2 reinfection in individuals with natural and hybrid immunity - Geehan Suleyman; Raef Fadel; Kunj Patel; Al Muthanna Shadid; Haim Bernardo Cotlear Stuart; Michael Kattula; Andrea Janis; Mohamed Maki; Shing Chao; George Alangaden; Indira Brar (Elsevier, 2023)
Background: Studies comparing SARS-CoV-2 reinfection outcomes among individuals with previous infection (natural immunity) and previous infection plus vaccination (hybrid immunity) are limited. Methods: Retrospective cohort study comparing SARS-CoV-2 reinfection among patients with hybrid immunity (cases) and natural immunity (controls) from March 2020 to February 2022. Reinfection was defined as positive PCR> 90 days after initial laboratory-confirmed SARS-CoV-2 infection. Outcomes included time to reinfection, symptom severity, COVID-19-related hospitalization, critical COVID-19 illness (need for intensive care unit, invasive mechanical ventilation, or death), length of stay (LOS). Results: A total of 773 (42%) vaccinated and 1073 (58%) unvaccinated patients with reinfection were included. Most patients (62.7%) were asymptomatic. Median time to reinfection was longer with hybrid immunity (391 [311−440] vs 294 [229−406] days, p < 0.001). Cases were less likely to be symptomatic (34.1% vs 39.6%, p = 0.001) or develop critical COVID-19 (2.3% vs 4.3%, p = 0.023). However, there was no significant difference in rates of COVID-19-related hospitalization (2.6% vs 3.8%, p = 0.142) or LOS (5 [2-9] vs 5 [3-10] days, p = 0.446). Boosted patients had longer time to reinfection (439 [IQR 372-467] vs 324 [IQR 256-414] days, p < 0.001) and were less likely to be symptomatic (26.8% vs 38%, p = 0.002) compared to unboosted patients. Rates of hospitalization, progression to critical illness and LOS were not significantly different between the two groups. Conclusions: Natural and hybrid immunity provided protection against SARS-CoV-2 reinfection and hospitalization. However, hybrid immunity conferred stronger protection against symptomatic disease and progression to critical illness and was associated with longer time to reinfection. The stronger protection conferred by hybrid immunity against severe outcomes due to COVID-19 should be emphasized with the public to further the vaccination effort, especially in high-risk individuals.